Citation databases and researcher identifiers - Yakimchik, A. I. (Geofizicheskiy Zhurnal, 2020)
Nowadays, there exist many resources available to find the scientific information, both commercial and free. Within the search and analysis of scientific publications, the intensive development of information technologies has led to the qualitative and even revolutionary changes. Despite the saturation of the market with technological tools, software, the tools for the information technologies and communications that surround the scientists, many of them are not used or used not enough because they are little known to the academic community. There is also no unique tool that can meet all the needs of scientists in the process of preparing and reviewing the articles. The main subject of this paper is the review and brief analysis of information resources and systems, identifiers and profiles of scientists. The basic search engines, citation databases, library information retrieval systems are described which can and should be used by a Ukrainian scientist to search for scientific literature. The differences between the search for information in commercial databases and the standard search on the Internet are considered. Examples of practical use of citation databases are given. Results of the research profiles of researchers at the Institute of Geophysics named after S.I. Subbotin testify to the lack of usage of Google Scholar services by scientists and the presence of considerable potential to increase the share of their visibility in world scientific and information flows. Only a third of all members of the Institute have a Google Scholar profile. It is shown that high citation statistics are based not only on the quality and relevance of scientific works, but also on the activity of the researcher in the modern media space. Recommendations are provided for registering and using the international ORCID Researcher (Open Researcher and Contributor ID).